Network meta-analysis of the efficacy of physical exercise interventions on vision health in children and adolescents - Liu, Jianming; Lan, Wencen; Zhang, Danxuan (Frontiers in Public Health, 2024)
Objective This study systematically evaluates the impact of different physical exercise modalities on vision health interventions for Chinese children and adolescents. Methods A comprehensive search was conducted in databases, including Web of Science, PubMed, EBSCO, MEDLINE, Embase, and CNKI. The focus was on randomized controlled trial (RCT) studies related to physical activity interventions for vision health in this demographic. The search covered literature from the inception of each database until May 1, 2023. Two researchers independently conducted literature screening, data extraction, and risk of bias assessment, adhering to pre-established inclusion and exclusion criteria. A network meta-analysis was performed using the “Network” package in Stata 14.2. Results The analysis encompassed 17 studies with 1,840 participants aged 7 to 18 years. Findings from the network meta-analysis revealed that badminton [MD = 0.23 (0.12, 0.33), p < 0.001] and table tennis [MD = 0.16 (0.09, 0.22), p < 0.001] exercises, along with health education [MD = 0.13 (0.03, 0.23), p = 0.013], were statistically significant in enhancing vision health compared to no intervention. According to the Surface Under the Cumulative Ranking (SUCRA) probability ranking, badminton (SUCRA = 96.7) and table tennis (SUCRA = 84.1) emerged as the most effective modalities for myopia intervention in children and adolescents, with health education (SUCRA = 73.2) following closely. Conclusion Physical exercise significantly contributes to the healthy development of vision in children and adolescents. Among various activities, badminton and table tennis are the most effective in improving visual health, highlighting the need for augmented promotion of visual health education. However, the quantity and quality of the included studies necessitate further high-quality intervention research to confirm these findings.